The Ongoing Development of Watch and Wait - Belkovsky, Mikhael; Alipouriani, Ali; Kanters, Arielle E.; Sommovilla, Joshua; Gorgun, Emre; Liska, David; Steele, Scott R. (Clinics in Colon and Rectal Surgery, 2024)
The nonoperative management of rectal cancer, known as watch and wait (W&W), has gained increasing acceptance in recent years. This approach is based on using complete clinical response (cCR) as a marker for complete pathological response (pCR) following neoadjuvant chemoradiation (nCRT). Advances in nCRT regimens have resulted in higher tumor regression rates, making W&W a viable option for selected patients. This study presents the historical evolution and efficacy of the W&W strategy and offers modern recommendations based on recent clinical findings. Key findings include an 85 to 92% 5-year disease-free survival rate in patients achieving cCR, highlighting the potential for improved quality of life and reduced morbidity without compromising survival outcomes.
Keywords: rectal cancer; watch and wait; nonoperative management